Faktor-Faktor yang Mempengaruhi Kualitas Hidup Pasien Chronic Kidney Disease (CKD) yang Menjalani Hemodialisa - Handi Rustandi; Hengky Tranado; Tinalia Pransasti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the factors that influence the quality of life of CKD patients undergoing hemodialysis at RSUD dr. M. Yunus Bengkulu in 2016. This type of research is descriptive research. The results showed almost all respondents had age <20 and> 35 years, more than some respondents were female, more than some respondents had sufficient income / more, almost some of the respondents had severe depression levels, more than some respondents had both in family support, more than most respondents have a high quality of life. Conclusion, there is a relationship between age, sex, income, depression, and family support with the quality of life of CKD patients undergoing hemodialysis. There is a relationship between family support and the quality of life of CKD patients undergoing hemodialysis. Keywords: Chronic Kidney Disease (CKD), Hemodialysis, Quality of Life